Public Participation after the Law- Making Procedure Law of 2022 - Fahmi Ramadhan Firdaus (Badan Strategi Kebijakan Hukum, 2022)
Constitutional Court Decision No. 91/PUU-XVIII/2020 affects Law no. 11 of 2020 concerning Job Creation. More than that, the Constitutional Court's decision seems to portray the fundamental problems of the law-making process that must be corrected immediately. These problems are, first, the Omnibus method in Law no. 12 of 2011 concerning the Establishment of Legislation. Second, procedural error and a change in the text after the mutual agreement. Third, ignoring meaningful public participation in the formation of laws. This research will focus on correcting the Constitutional Court to the process of law formation to prioritize meaningful participation, not just a mere formality. The legislators then followed up the Constitutional Court's notes by revising Law no. 12 of 2011 concerning the Establishment of Legislation for the second time become Law no. 13 of 2022, one of the substances of which is to change the provisions of Article 96, which contains the regulation of public participation in the formation of laws. The formulations of the problem raised in this study are: what is the meaning of meaningful public participation in the construction of rules based on the Constitutional Court Decision No. 91/PUU-XVIII/2020, and what is the ideal arrangement in Law no. 12 of 2011 concerning the Formation of Legislations to accommodate meaningful participation in the formation of laws. This study found that Law no. 13 of 2022 cannot accommodate meaningful participation because it is still a right and not an obligation. Then legislators must create information technology-based tools that help increase meaningful participation in law-making.